Postoperative Recovery Outcomes for Obese Patients Undergoing General Anesthesia: A Meta-Analysis of Randomized Controlled Trials - Hu, Zhen-Hua; Liu, Zhe; Zheng, Gai-Fang; Li, Zhan-Wen; Liu, Sheng-Qun (Frontiers in Surgery, 2022)
Purpose This study was performed to assess the postoperative recovery outcomes in obese patients undergoing general anesthesia. Methods The eligible studies were identified from PubMed, EmBase, and the Cochrane library until December 2020. The standard mean differences (SMDs) with 95% confidence intervals (CIs) were used to calculate the role of desflurane, sevoflurane, and propofol on recovery outcomes, and the analyses using the random-effects model. Results Eleven randomized controlled trials involving 713 obese patients undergoing general anesthesia were selected for final meta-analysis. We noted desflurane was associated with a shorter time to eye-opening than sevoflurane (SMD: −0.86; 95% CI, −1.43 to −0.28; P = 0.003). The use of desflurane with shorter time to extubation as compared with propofol (SMD: −1.13; 95% CI, −1.52 to −0.73; P < 0.001) or sevoflurane (SMD: −1.19; 95% CI, −2.15 to −0.22; P = 0.016), while sevoflurane was associated with longer time to extubation as compared with propofol (SMD: 1.47; 95% CI, 1.03 to 1.91; P < 0.001). Desflurane were associated with shorter time to stating name as compared with propofol (SMD: −1.40; 95% CI, −2.32 to −0.48; P = 0.003) or sevoflurane (SMD: −2.09; 95% CI, −3.33 to −0.85; P = 0.001). In addition, desflurane was associated with a longer time for orientation to place as compared with propofol (SMD: 0.65; 95% CI, 0.22 to 1.07; P = 0.003), while desflurane with shorter time for orientation to place as compared with sevoflurane (SMD: −0.88; 95% CI, −1.46 to −0.30; P = 0.003). Conclusions The use of desflurane could provide better recovery outcomes in obese patients undergoing general anesthesia. Further large-scale trials should be comparison the long-term effectiveness of various anesthetics.